ARYLSULFATASE - PRODUCING BACTERIA IN MARINE SEDIMENTS - DHEVENDARAN, K; CHANDRAMOHAN, D; NATARAJAN, R (Fishery Technology, 2017)
A total of 313 strains of bacteria which hydrolysed tripotassium phenolphthalein disulfate (PDS) were isolated from the sediments of three biotopes, namely, Vellar estuary, backwater and mangrove during the period of investigation. They were identified to the generic level. The following genera were encountered, namely, Vibrio, Bacillus, Alcaligenes, Micrococcus, Pseudomonas, Cytophaga - Flavobacterium,Aeromonas, Corynebacterium and members of Enterobacteriaceae. Vibrio and Bacillus were found to be the dom ant groups representing 29.26% and 41.80% respectively of the total isolates .. Because of the importance of the Vibrio group in marine environment these isolates were further identified to the species level and it included V. parahaemolyticus, V. alginolyticus, V. consticola, V. anguillarum andV. fischeri. These observations suggest that different groups of arylsulfatase - producing bacteria probably occur in marine sediments.